The Role of Alumni in Improving School Marketing - Liesa Anggraeeny; Renny oktafia; Hidayatulloh Hidayatulloh (Proceedings of The ICECRS, 2020)
In the amid of the educational institutions growth, there is strict competition with the various advantages offered, schools that still want to exist in the fields should have an effective marketing strategy to recrut learners as a key component in the education system. Many marketing strategies are avaiable, part of it is promotion. In the promotion there is a Word of mouth Marketing model. Researchers assumed that this promotion model was more effective and efficient when it gained the support of alumni roles as a school product that had strong ties with his almamater. The quality of the alumni is a reflection of the quality of the institution hence to influence the community in choosing a quality school. What differs from other research is the author elevating the important role of alumni in school marketing. The purpose of this research is to describe the important role of alumni for schools and the role of alumni in improving school marketing. Data was taken from literature, alumni interviews related to alumni and observation roles. The results of the study showed the strategic and potential of the alumni role should be recognized and utilized for school development. The role of alumni include: Develop extracurricular activities, build opinions on the quality of the school in the community, build networks outside of the school, become motivators and Inspirators for the sister of her class, become a companion of learning, supporting activities organized by the school, and the evaluation media for the school curriculum. The role of alumni in improving school marketing is very high. This is because the perception of schools developing in the community as consumers are influenced by the quality of alumni as a school product, the quality of alumni supports the promotion of schools in the community as well as information about schools obtained directly through alumni.